Method for determining porosity of shale oil sample with effective pore space

By controlling the self-priming saturation time of shale oil samples and using specific oil dehumidification and dehumidification techniques, the problem of inaccurate porosity measurement of shale oil samples in the prior art is solved, and high accuracy and high efficiency porosity measurement is achieved.

CN119534259AActive Publication Date: 2025-02-28DAQING OILFIELD CO LTD +1

Patent Information

Application Number
CN202311110829.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-02-28
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

The prior art is difficult to accurately determine the effective porosity of shale oil samples, especially in the errors caused by poor oil and gas discharge and clay water loss.

Method used

By controlling the self-priming saturation time of the sample, the saturated liquid is prevented from entering the clay adsorption layer, the degreasing trichloromethane and vacuum 60℃ and 8h dehumidification technology are used to ensure the separation of pore water and clay adsorbed water, and the porosity of the sample is accurately measured.

Benefits of technology

The accurate determination of the effective porosity of shale oil samples is achieved, which reduces the experimental cycle, improves the accuracy and reliability of the measurement, and avoids errors caused by poor oil and gas discharge and clay water loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534259A_ABST
    Figure CN119534259A_ABST
Patent Text Reader

Abstract

The invention discloses a method for determining porosity of a shale oil sample in an effective pore space. The method mainly solves the problem that the porosity of an effective storage space cannot be accurately measured due to cracks caused by unsmooth oil-gas separation of the existing oil-containing shale and loss of clay water. The method is characterized by comprising the following steps: S1, preparing a shale sample; s2, putting the sample into a saturated solution for self-absorption saturation, and recording the self-absorption saturation time; s3, measuring the crane scale mass of the sample in the saturated liquid and the wet sample mass of the sample full of the saturated liquid, measuring the density of the saturated liquid, and calculating the total volume of the sample; s4, performing oil removal, ventilation and dehumidification on the sample; s5, measuring the mass of a dry sample and the volume of a sample skeleton, and measuring the mass of particles and dust in the sample bag; and S6, calculating the porosity of the shale sample. According to the method, the influence caused by cracks generated by dehydration of the sample is eliminated, the effective porosity of the shale oil sample in which the clay adsorbed water is retained in situ and the pore water is removed can be accurately determined, the experimental period is short, and the accuracy is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of oil and gas exploration and development experimental testing, and in particular to a method for determining the porosity of a shale oil sample in effective pore space. Background Art

[0002] The exploration and development of shale oil and gas has become an important field of oil and gas exploration and development in the world. Due to the special characteristics of shale, many previous exploration and development technologies are difficult to adapt to the needs of shale. Porosity is an indispensable parameter for the exploration and development of shale oil and gas, and its analysis method is also affected by lithology. Shale oil reservoir samples have developed bedding fissures, which are very easy to produce cracks and breakages, and will produce cracks when exposed to water or dehydrated. In previous methods, the non-complete saturation method and the method of "first measuring the total volume and then removing oil and moisture" were used to solve the problem of inaccurate porosity measurement caused by cracks and deformation of shale samples due to dehumidification during porosity measurement of shale oil samples. The use of the non-completely saturated method can solve the problem of cracks in shale samples due to saturation. This method stipulates that the total volume of the sample should be measured before the sample is fully saturated, avoiding the inaccurate porosity measurement caused by cracks in the sample after it is fully saturated. However, it only considers the problem of inaccurate pore measurement caused by the increase in total volume due to cracks in the sample after it is fully saturated, but does not consider the problem that the saturated liquid (such as ethanol) enters the clay adsorption layer to replace the clay adsorbed water, causing the clay adsorbed water to escape, resulting in a smaller skeleton volume measurement and a larger porosity measurement with a loss of accuracy. The problem of inaccurate porosity measurement caused by saturated liquid infiltrating the clay adsorption layer is becoming more and more obvious, and this problem needs to be studied and solved as soon as possible.

[0003] Shale is dense, and oil and gas exist in nano and micro-nano pores. Oil and gas seepage is controlled by pore distribution. Due to the use of freezing technology in shale oil reservoir pressure-maintained cores, oil and gas are sealed in pores. When the pressure-maintained samples are thawed and slowly melted, some samples are blocked from oil and gas escape. Under the action of the internal pressure of the fluid, shale oil samples will crack along the bedding plane and produce cracks, which will also affect the accuracy of porosity measurement. At present, there is no good way to solve the problem of inaccurate porosity measurement caused by cracks caused by poor oil and gas escape.

[0004] Another characteristic that affects the porosity determination is the clay mineral composition of shale. Clay minerals are rich in water, including not only pore water but also clay-adsorbed water. Clay-adsorbed water is water retained in the interlayer domain by adsorption, most of which is adsorbed on the surface of clay particles and does not occupy effective pore space. Clay has a large specific surface area and a high content of clay-adsorbed water. Moreover, it can also be released at about 100°C together with pore water. The porosity of the same shale sample that retains clay-adsorbed water and that that releases clay-adsorbed water is quite different. In the exploration and development of shale oil and gas, the porosity parameters containing clay-adsorbed water and that that releases clay-adsorbed water have different application values. In particular, the porosity of shale that retains clay-adsorbed water, i.e., effective pore space, is indispensable in reservoir research, reserve evaluation and other studies.

[0005] There is no good experimental method to retain the clay-adsorbed water in situ in oil-bearing shale and only remove the pore water. At present, there is no experimental method of our own. We borrow the technology of removing pore water from non-oil-bearing shale, that is, to constant weight under vacuum conditions of 60°C. The general practice of this method is to dry the sample under vacuum conditions of 60°C for 4 hours, cool it to room temperature in a dryer, weigh it, and then use the same method to dry and weigh it until the sample weight is constant. For non-oil-bearing shale, it usually takes 3-4 times to dry a batch of samples to constant weight. Due to the long experimental cycle, clay water has been lost and the experimental error is large. For shale oil reservoir samples, due to the oil content in the samples and the loss of different oil and gas, it is more difficult to keep a constant weight of the samples under vacuum at 60°C, the experimental cycle is longer, and the loss of clay water is greater, which will cause a greater error in the determination of effective porosity. Therefore, the application of pore water removal technology for oil-free shale to shale oil reservoir samples will produce greater errors, and the accuracy of sample analysis cannot be guaranteed. There is also a lack of effective methods for determining the effective pore space porosity of shale oil reservoir samples that retain clay-adsorbed water in situ and remove pore water. Summary of the invention

[0006] In order to overcome the problem that the existing oil-bearing shale is unable to accurately measure the porosity of the effective storage space due to cracks caused by the poor oil and gas escape and the loss of clay water, the present invention provides a method for measuring the porosity of shale oil samples in effective pore space. The method eliminates or partially eliminates the influence of cracks in the core caused by the rapid release of fluid pressure in the pores of the shale oil sample on the porosity analysis, avoids the disadvantage of inaccurate porosity measurement caused by clay water escape due to different reasons in the process of porosity measurement of the effective pore space of the shale oil reservoir sample, and can accurately measure the effective porosity of the shale oil sample that retains the clay adsorbed water in situ and removes the pore water, and has a short experimental period and high accuracy.

[0007] The technical solution of the present invention is: a method for determining the porosity of a shale oil sample in effective pore space, comprising the following steps:

[0008] S1. Prepare shale samples;

[0009] S2. Place the sample in a saturated liquid for self-absorption and saturation, and record the self-absorption saturation time;

[0010] S3. Measure the mass M2 of the sample in the saturated liquid and the mass M1 of the wet sample saturated with the saturated liquid, and determine the density ρ1 of the saturated liquid, and calculate the total volume V of the sample:

[0011]

[0012] Where: V—total volume of the sample being tested, cm 3 ; M2—the mass of the sample on the hanging scale after it is saturated with saturated liquid, g; M1—the mass of the wet sample after it is saturated with saturated liquid, g; ρ1—the density of saturated liquid, g / ml;

[0013] S4. Degrease, ventilate and dehumidify the samples;

[0014] S5. Measure the dry sample mass m1 and the sample skeleton volume V m1 , and measure the mass m2 of particles and dust in the sample bag;

[0015] S6. Calculate the porosity φ of shale samples:

[0016]

[0017] Where: V m1 —Sample skeleton volume, cm 3 ; m2—mass of particles and dust falling off in the sample bag, g; m1—mass of dry sample, g; φ—effective porosity of the sample being tested, %.

[0018] Furthermore, for samples with visible cracks, the total volume correction of the crack samples was performed: the samples were separated along the cracks, and a large piece without cracks was taken as the crack sample. After self-absorption saturation, the hanging scale mass m3 of the crack sample and the wet sample mass m4 of the crack sample were measured. After the crack sample was degreased, ventilated, and dehumidified, the dry sample mass m5 of the crack sample was measured, and the total volume V of the crack sample was calculated. t :

[0019]

[0020] Where: m3—the mass of the hanging scale of the fracture sample, g; m4—the mass of the wet sample of the fracture sample, g; m5—the mass of the dry sample of the fracture sample, g; V t —Total volume of fractured sample, cm 3 ;

[0021] At this time, the sample porosity φ is:

[0022]

[0023] Further, the step S1 comprises:

[0024] S1.1. Freeze the full-diameter sample of the shale oil reservoir from which the sample to be tested is prepared;

[0025] S1.2. Cutting full-diameter sheet samples of required thickness from full-diameter samples of shale oil reservoirs;

[0026] S1.3. Use a cutting tool to cut the full-diameter flaky sample into shale samples of the required size in a direction perpendicular to the bedding and the bedding end surface.

[0027] Furthermore, in step S1, the cryo-prepared sample is frozen by liquid nitrogen.

[0028] Furthermore, in step S2, the saturated liquid is anhydrous ethanol or kerosene.

[0029] Furthermore, in step S2, the saturated liquid of the shale sample without oil is anhydrous ethanol, and the saturated liquid of the shale sample containing oil is anhydrous ethanol or kerosene.

[0030] Further, in step S2,

[0031] t<T p (5)

[0032] Where t is the longest time for the sample to be saturated by self-absorption; T p —The time it takes for the saturated liquid to penetrate into the clay adsorption layer or produce cracks.

[0033] Further, in step S2,

[0034]

[0035] Where: t is the longest time of self-absorption saturation, t0 is the sample self-absorption saturation time corresponding to a certain stable time interval (△t), is the average time used to test each sample, and n is the number of self-absorption saturated samples.

[0036] Furthermore, in step S4, chloroform is used as a degreasing agent for degreasing the sample. After degreasing, the sample and the sample bag are ventilated for 4h-8h, and then the sample and the sample bag are placed in a vacuum drying oven, dried at 60°C in vacuum for 8h, and then taken out.

[0037] The present invention has the following beneficial effects: Due to the adoption of the above scheme, (1) the present invention controls or limits the self-imbibition saturation time of the sample to be tested, so that the total volume of the sample is measured before the sample saturation liquid has immersed in the clay adsorption layer of the shale sample, thereby avoiding the disadvantage of inaccurate porosity (total volume) measurement caused by the outflow of water from the clay adsorption layer or the partial / full saturation of the sample during the saturation process. (2) The total volume of the sample is measured first, and then the skeleton volume of the sample is measured by deoiling and dehumidifying, thereby avoiding the disadvantage of the previous method of first deoiling and dehumidifying and then measuring the total volume, which causes cracks in the mud shale sample and brings errors to the porosity measurement result, thereby improving the accuracy of the effective porosity measurement of shale oil samples. (3) Taking advantage of the fact that chloroform dissolves oil but not water, chloroform was selected as the oil removal agent to ensure that the pore water and clay-adsorbed water in the sample were not destroyed. The total volume measurement technology that limited the self-imbibition saturation time to prevent the saturated liquid from entering the clay layer and the dehumidification technology of "vacuum 60℃8h" to remove pore water were used to effectively remove the pore water and retain the clay-adsorbed water in situ, ensuring the accuracy of the skeleton volume measurement, avoiding the disadvantage of reduced accuracy of porosity (skeleton volume) measurement due to clay water outflow, and improving the accuracy, reliability and work efficiency of the effective porosity measurement of shale oil samples that retain clay-adsorbed water. (4) Further, a part of the sample without visible cracks was used for total volume correction measurement to eliminate the influence of cracks in the shale on the porosity caused by the poor discharge of fluid in the shale. (5) The "vacuum 60℃ 8h" dehumidification technology provided by the method of the present invention provides an effective experimental technology for removing only pore water and retaining pore water in situ for oil-bearing shale. Moreover, dehumidification and drying for 8h under vacuum 60℃ conditions avoids repeated experimental work such as vacuum heating and weighing, shortens the experimental cycle, reduces labor intensity, and improves work efficiency. At the same time, the present invention has the advantages of the HSE analysis and testing concept of health, safety, and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a flow chart of the present invention;

[0039] Figure 2 This is a graph showing the change in porosity at different dehumidification times. DETAILED DESCRIPTION

[0040] The present invention will be further described below:

[0041] Depend on Figure 1 As shown, a method for determining the porosity of a shale oil sample with effective pore space comprises the following steps:

[0042] S1. Prepare shale samples, specifically:

[0043] S1.1. Use liquid nitrogen, dry ice or freezer to freeze the full-diameter shale oil reservoir samples for parallel sample preparation, preferably liquid nitrogen freezing. Shale oil samples have developed stratification. Under the action of external force, the samples will break or shatter along the stratification plane. For fresh samples (i.e., there is no large amount of oil and water loss in the samples), the water in the samples acts as a consolidating adhesive, bonding the particles and the stratification together, which can resist the external force to the greatest extent. Therefore, the hardness of the frozen samples increases, the resistance to crushing is enhanced, and the success rate of sample preparation can be improved.

[0044] S1.2. At the sampling depth of the frozen full-diameter sample of the shale oil reservoir, under liquid nitrogen cooling, use a core cutting tool to cut a full-diameter sheet sample of the required thickness along the core bedding plane. The sample thickness is generally 15mm-20mm, which is determined according to different analysis samples.

[0045] S1.3. Cut the full-diameter flaky sample into shale samples of the required size using a cutting tool in a direction perpendicular to the bedding and the end face of the bedding. Using a tool to cut the sample can avoid breaking the sample, greatly improve the success rate of the sample, and can produce samples at any position as required. The tool should be perpendicular to the end face of the bedding during cutting, so that the sample can avoid cracks or splits along the bedding surface.

[0046] S2. Immerse the shale samples to be tested in the saturated liquid in the container according to the number, so that the samples are saturated by self-absorption. The saturated liquid is anhydrous ethanol or kerosene. Among them, oil-free samples (such as oil-free mudstone and mud shale, shale gas, shale oil samples that have been deoiled, etc.) are generally saturated with anhydrous ethanol. If the oil-free samples are saturated with kerosene, the oil must be completely removed during the porosity analysis, which is time-consuming and labor-intensive compared with saturated anhydrous ethanol. The experimental cycle is much longer, which greatly reduces the work efficiency. In addition, chemical reagents are used for deoiling. The deoiling chemical reagents used are all toxic and harmful substances, which are harmful to the environment and human health. Therefore, ethanol is used to saturate the oil-free samples as much as possible. Oil-containing samples are generally saturated with kerosene, and can also be saturated with anhydrous ethanol.

[0047] Record the self-imbibition saturation time: select a sample of appropriate mass and volume, place the sample in the hanging net in the beaker of the buoyancy measuring device, use a stopwatch to time, observe the balance reading at the same time, and record the sample's self-imbibition saturation time.

[0048] The purpose of determining the self-absorption saturation time is to minimize or avoid the saturated liquid from entering the clay adsorption layer area, and to avoid cracks or breakage of the sample after the sample is saturated to a certain degree. The saturated liquid will extract water from the adsorption layer when it enters the clay adsorption layer. When the sample is dehumidified, the saturated liquid will escape, and the adsorption layer will produce pores, resulting in a larger porosity measurement, which will reduce the accuracy of the effective porosity measurement. In order to accurately determine the porosity of the sample with effective pore space, it is necessary to avoid ethanol from entering the clay adsorption layer or the sample from producing cracks or even breaking. Therefore, the maximum self-absorption saturation time t of the sample should meet the following requirements:

[0049] t<T p (5)

[0050] Where t is the longest time for the sample to be saturated by self-absorption; T p —The time it takes for the saturated liquid to penetrate into the clay adsorption layer or produce cracks.

[0051] At the same time, the maximum self-absorption saturation time of the sample t

[0052]

[0053] Where: t is the longest time of self-absorption saturation, t0 is the sample self-absorption saturation time corresponding to a certain stable time interval, is the average time used to test each sample, and n is the number of self-absorption saturated samples.

[0054] To satisfy t<T p , it is necessary to select an appropriate t0 and the number of self-absorption saturated samples n. p In the case of a small amount, that is, when the pore permeability of the tested shale sample is good (such as medium-shallow mudstone), or the pore water content of the sample is small due to loss, or the pore water content of the sample itself is low (such as deep shale with a long storage time), T p will become smaller. At this time, a smaller t0 should be selected as much as possible, or the number of self-absorption saturated samples should be reduced to meet the above relationship. p The determination can be carried out by nuclear magnetic resonance experiments with different self-imbibition saturation times. However, the lithology of mudstone is relatively dense. When a smaller stable time interval is selected for determination, the time used is much shorter than the self-imbibition saturation time t0 corresponding to the maximum stable time interval measured by the self-imbibition saturation time determination experiment. The maximum self-imbibition saturation time (denoted as t 0最大 ) as T p , that is, when When T P ≈t 0最大 , t 较小 is the minimum self-priming saturation time, t 0最大 The maximum self-priming saturation time was obtained experimentally.

[0055] In general, for dense shales with little water loss, the maximum time for sample self-imbibition saturation t is within 1h~2h, and t0 can be selected from a stable time interval of several seconds to several minutes, or even more than ten minutes and the corresponding self-imbibition saturation time t0, and the number of saturated samples can be up to 40 to 50; for dense shale samples with large pore water loss and low pore water, the stable time interval can be selected from several minutes or tens of seconds or even seconds according to the experimental data and the specific conditions of the samples. The number of self-imbibition samples is 10~20, or even several samples are self-imbibition saturated, or the total volume of a single sample is directly determined by the method of determining the self-imbibition saturation time; for medium and shallow mudstones, mud shales and dense shales with less pore water are similar, and are determined according to experiments and lithology. The same self-imbibition saturation time can be used for the same type of mud shales in the same reservoir in the same area, and one experiment is sufficient.

[0056] S3. Using the Archimedean buoyancy measuring device, after self-saturation, measure the mass M2 of the sample in the saturated liquid and the mass M1 of the wet sample saturated with the saturated liquid. It takes about 5 seconds from reading the balance to taking out the sample and wiping off the attached liquid on the surface of the sample. The measuring balance is a one-thousandth balance. In order to improve the accuracy of sample measurement, a dynamic rapid total volume measurement method can be used, that is, the sample is measured while self-saturating, and the two masses are measured before the one-thousandth balance reading does not change.

[0057] Use a densitometer to measure the saturated liquid density ρ1 and calculate the total volume V of the sample:

[0058]

[0059] Where: V—total volume of the sample being tested, cm 3 ; M2—the mass of the sample on the hanging scale after it is saturated with saturated liquid, g; M1—the mass of the wet sample after it is saturated with saturated liquid, g; ρ1—the density of saturated liquid, g / ml.

[0060] S4. Degrease, ventilate and dehumidify the samples.

[0061] S4.1. Oil removal. Place the sample in a dry sample bag with a known mass and a corresponding number to the sample, use chloroform, which has a low boiling point and is insoluble in water, as an oil removal reagent, and do not destroy the clay adsorbed water and pore water in the sample. Use a Soxhlet extractor and follow the prescribed operating procedures to remove the oil. After oil removal, take out the sample (together with the sample bag) from the Soxhlet extractor and place it in a fume hood for 4 to 8 hours to volatilize part of the reagent in the sample bag and the sample.

[0062] S4.2, Dehumidification. Place the sample to be tested (together with the sample bag) in a vacuum drying oven, dry it at 60°C in vacuum for 8 hours, then take it out and place it in a desiccator. Alternatively, take the sample out of the sample bag, place the sample and the sample bag in a vacuum drying oven at the same time, dry it at 60°C in vacuum for 8 hours, then take out the sample and the sample bag and place them in a desiccator.

[0063] S5. Measure the dry sample mass m1 and the sample skeleton volume V m1 , and measure the mass m2 of particles and dust in the sample bag. The gas injection method is used to determine the sample skeleton volume, the purpose of which is to obtain the pore volume or porosity in combination with the total volume. During the degreasing process, some samples have particles and / or dust falling off. The dust and particle skeleton volume can be calculated by particle density, so it does not need to be measured directly. For crushed samples, the sample skeleton volume can be directly measured after crushing.

[0064] S6. Calculate the porosity φ of the shale sample according to the data in steps S2 and S5:

[0065]

[0066] Where: V m1 —Sample skeleton volume, cm 3 ; m2—mass of particles and dust falling off in the sample bag, g; m1—mass of dry sample, g; φ—effective porosity of the sample being tested, %.

[0067] In addition, for samples with visible cracks, the total volume of the cracked samples is corrected, and the total volume of the shale samples without cracks is measured. For shale samples with good homogeneity, the total volume of the tested samples can be obtained by the density of the partial samples, which can eliminate the influence of cracks and have a certain calibration effect on the inaccurate total volume caused by the cracks caused by the escape of fluid in the original shale samples before they are separated along the cracks. This method is suitable for samples with visible cracks.

[0068] The sample is separated along the cracks, and a piece without cracks and with a large volume is taken as the crack sample. After self-absorption saturation, the hanging scale mass m3 of the crack sample and the wet sample mass m4 of the crack sample are measured according to the method of steps S3-S5. After the crack sample is degreased, ventilated, and dehumidified, the dry sample mass m5 of the crack sample is measured, and the total volume V of the crack sample is calculated. t :

[0069]

[0070] Where: m3—the mass of the hanging scale of the fracture sample, g; m4—the mass of the wet sample of the fracture sample, g; m5—the mass of the dry sample of the fracture sample, g; V t —Total volume of fractured sample, cm 3 .

[0071] At this time, the sample porosity φ is:

[0072]

[0073] The following is further explained with experiments.

[0074] Shale oil reservoir samples were selected and some experiments were carried out to determine the technical conditions for porosity determination.

[0075] Experiment 1: Pore water removal experiment

[0076] The researchers of this application found that although both pore water and clay-absorbed water can be released at about 100°C, the areas where pore water and clay-absorbed water exist in the rock core are different. Among them, most of the clay-absorbed water is adsorbed on the surface of clay particles, and pore water exists in the pores of rocks. The surface tension (that is, gravity) of the rock particle surface on water gradually increases from the center of the rock pore to the surface of the rock particle. Under the action of temperature and vacuum conditions, the pore water and clay-absorbed water of the rock have a sequence of release, and the pore water is released first. In order to verify this discovery, the experimental method of retaining clay-absorbed water in situ and only releasing pore water was studied, and corresponding experiments were carried out. The specific experimental methods and results are as follows.

[0077] The experimental samples were selected from the shale oil layer samples of Well XX1. After the core was lifted from the wellbore to the ground, the required samples were obtained from the middle part of the core. The sample thickness was about 15 mm, the average length and width were 25 mm and 19 mm respectively, and the mass was 17.753 g. Due to conventional coring, the light hydrocarbons in the sample were lost during the process of lifting the core from the wellbore to the ground, but the pore water and clay adsorbed water in the core were basically distributed under the formation conditions.

[0078] In order to avoid the loss of water in the samples, they were frozen with liquid nitrogen and transported back to the laboratory. Nuclear magnetic resonance measurement was carried out immediately after thawing. The samples were then placed in a vacuum drying oven, evacuated, and heated to 60°C. The samples were kept in a vacuum state and dried at 60°C for 10 hours.

[0079] In order to understand the changes in clay-adsorbed water and pore water in the sample, two-dimensional nuclear magnetic resonance detection was performed every 2 hours to obtain nuclear magnetic distribution spectrum data at different times. Two-dimensional nuclear magnetic resonance analysis can separate pore water from structural water / crystallized water / clay-adsorbed water, oil from organic matter / asphalt, and oil from water, so four sets of data can be obtained, as shown in Table 1 below.

[0080] Table 1 2D NMR analysis data of shale

[0081]

[0082] It can be seen from the experimental data in Table 1 that the data of structural water / crystallization water / clay adsorbed water and organic matter / asphalt determination remain basically unchanged, and the test data at different times are slightly different. The clay adsorbed water in the structural water / crystallization water / clay adsorbed water does not flow out. As the experimental time increases, the amount of water in the sample gradually decreases, and the reduction amplitude becomes smaller and smaller. When the drying time reaches 8h, the pore water content is less than 0.02mL, and when the same time is increased, the pore water of the tested sample changes very little. Therefore, the shale oil sample tested is dried at 60℃ in vacuum for 8h, and the pore water content is less than 0.02mL, which can meet the accuracy requirements of geological experiments. Oil is in a decreasing trend with the increase of drying time. For oil-bearing shale samples, the mass constant method is used to determine the pore water. The oil removal will affect the degree of change in the sample mass. This shows that the oil-bearing shale samples are not suitable for the mass constant method to determine the pore water due to the loss of oil and gas during the heating and dehydration process.

[0083] Repeated experiments on shale oil samples of different geometric sizes have shown that the optimal release time of pore water under vacuum and 60°C is 8 hours.

[0084] Experiment 2: Porosity measurement experiment at different self-imbibition saturation times

[0085] In order to understand the similarities and differences in the porosity of the effective storage space of different self-absorption packages and time samples, shale samples in the exploration area were selected, and two groups of parallel samples were prepared by cutting method. Preparation method: On the full-diameter shale samples, a full-diameter sheet sample with a thickness of 14mm-22mm was made along the core sedimentary bedding plane under liquid nitrogen refrigeration using a proprietary tool. On the sample, a cutting tool was used to cut along the direction perpendicular to the bedding and the bedding end surface into an approximately rectangular sample with a length of 40mm-60mm and a width of 18mm-25mm. The sample was then cut into two parallel samples, and the sample was randomly divided into two groups A and B, with a total of 11 samples in each group. Analysis method: The samples were immersed in anhydrous ethanol at the same time. The total volume of the sample was measured after the self-absorption saturation of the sample in group A for 15min, and the total measurement time was approximately 10min. The saturation and measurement time of the sample in group A was 25min, and then the sample was placed in a specific container for sealing. The total volume of group B samples was measured after self-absorption saturation for 150 minutes. The total time for sample saturation and measurement was approximately 160 minutes. After the measurement, the two groups of samples were respectively placed in cloth bags corresponding to the sample numbers. The two groups of samples were mixed together and placed in the same Soxhlet extractor for deoiling with chloroform for 72 hours. After deoiling, the samples were placed in a vacuum drying oven for dehumidification and kept at 60°C in vacuum for 8 hours. The gas injection method was then used to measure the sample skeleton volume, and the porosity of the measured sample was obtained.

[0086] The experimental results are shown in Table 2.

[0087] Table 2 Experimental data of porosity determination under different self-imbibition saturation time

[0088]

[0089] From Table 2, we can see that the porosity of group B samples is greater than that of group A samples. Except for the self-imbibition saturation time, the other test conditions and test methods of the two groups of samples are the same. Since the self-imbibition saturation time of group B samples is too long, ethanol penetrates into the clay adsorption layer, resulting in a larger porosity.

[0090] Experiment 3: Porosity measurement experiment at different dehumidification times

[0091] Three shale oil reservoir samples were selected to carry out porosity measurement experiments. The method was: after sample preparation, they were immersed in anhydrous ethanol for 15 minutes, the total volume of the samples was measured, and then chloroform was used to remove oil, and then dehumidified at 60℃ for 8 hours in vacuum, and then dehumidified at 105℃ to constant weight. In order to study the time-varying characteristics of porosity, the skeleton volume of the samples was measured every 1 hour during each dehumidification at 60℃ for 8 hours in vacuum, and the initial time for measuring the skeleton volume was 3 hours of dehumidification.

[0092] The experimental results are shown in Figure 2 Before the sample was placed in vacuum at 60℃ for 6h, the porosity of the sample increased linearly with time. After 6h, the porosity of the sample changed slowly and the difference was not large. At 7h-9h, the porosity curve of each sample had a smooth section and the porosity was approximately the same. After 10h, the porosity increased, and the porosity at 105℃ was greatly increased when dehumidified to constant weight. Combined with the pore water removal experiment in Experiment 1, the pore water of the sample was almost removed at 7h-9h, while the clay adsorbed water was retained in situ. The porosity in this period was the effective porosity of the clay adsorbed water retained in situ and only the pore water was removed. Therefore, under the vacuum condition of 60℃, drying for 8h is the best time to remove the pore water, and the porosity obtained can truly reflect the porosity of the effective pore space.

[0093] Experiment 4: Sample Analysis

[0094] At present, shale oil is one of the hot spots in oil and gas exploration and development. The porosity of the effective pore space of shale oil reservoir samples is indispensable data for reservoir research and reservoir understanding. For this purpose, a large number of sample analysis work has been carried out. Table 3 is the analysis results according to the method of the present invention. In order to illustrate the influence of clay adsorbed water on porosity, after the analysis according to the method of the present invention, the samples were dehumidified to constant weight in a 105°C drying thermostatic box. After removing the clay adsorbed water of the samples, the sample skeleton volume was measured to obtain the effective porosity after removing the clay adsorbed water.

[0095] From the analysis data (see Table 3), the porosity measured by the method of the present invention is generally smaller than the porosity after removing the clay adsorbed water, with a maximum difference of 3.3%, a minimum difference of 1.8%, and an average of 2.5%, indicating that the clay adsorbed water has a great influence on the porosity of the shale oil rock sample. In actual testing, the experimental technology of controlling or limiting the removal of clay adsorbed water should be used as much as possible to determine the effective pore space porosity of the shale oil rock sample. It can be seen that the porosity determination method for limiting the removal of clay adsorbed water in shale oil rock samples provided by the present invention can better reflect the actual situation of the porosity change of the effective pore space of the shale oil rock sample, which is of great value to the exploration and development of shale oil and gas.

[0096] Table 3 Comparison of sample analysis data

[0097]

[0098]

[0099] The above-mentioned embodiments are only embodiments of the present disclosure, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present disclosure. It should be pointed out that, for ordinary technicians in this field, several variations, equivalent substitutions, improvements, etc. can be made without departing from the concept of the present disclosure, and these all belong to the protection scope of the present disclosure.

Claims

1. A method for determining the porosity of shale oil samples in terms of effective pore space, characterized in that The following steps are involved: S1. Prepare shale samples; S2. Place the sample in a saturated liquid for self-absorption and saturation, and record the self-absorption saturation time; S3. Measure the mass M2 of the sample in the saturated liquid and the mass M1 of the wet sample saturated with the saturated liquid, and determine the density ρ1 of the saturated liquid, and calculate the total volume V of the sample: Where: V-total volume of the sample being tested, cm 3 ; M2-the mass of the sample on the hanging scale after it is saturated with saturated liquid, g; M1-the mass of the wet sample after it is saturated with saturated liquid, g; ρ1-the density of saturated liquid, g / ml; S4. Degrease, ventilate and dehumidify the samples; S5. Measure the dry sample mass m1 and the sample skeleton volume V m1 , and measure the mass m2 of particles and dust in the sample bag; S6. Calculate the porosity φ of shale samples: Where: V m1 - Sample skeleton volume, cm 3 ; m2-mass of particles and dust falling out of the sample bag, g; m1-dry sample mass, g; φ-effective porosity of the sample under test, %.

2. The method for determining the porosity of shale oil samples in effective pore space according to claim 1, characterized in that: For samples with visible cracks, the total volume correction of the crack samples is performed: the samples are separated along the cracks, and a large piece without cracks is taken as the crack sample. After self-absorption saturation, the hanging scale mass m3 of the crack sample and the wet sample mass m4 of the crack sample are measured. After the crack sample is degreased, ventilated, and dehumidified, the dry sample mass m5 of the crack sample is measured, and the total volume V of the crack sample is calculated. t : Where: m3—the mass of the hanging scale of the fracture sample, g; m4—the mass of the wet sample of the fracture sample, g; m5—dry sample mass of fracture sample, g; V t —Total volume of fractured sample, cm 3 ; At this time, the sample porosity φ is:

3. The method for determining the porosity of shale oil samples in effective pore space according to claim 1 or 2, characterized in that: The step S1 comprises: S1.

1. Freeze the full-diameter sample of the shale oil reservoir from which the sample to be tested is prepared; S1.

2. Cutting full-diameter sheet samples of required thickness from full-diameter samples of shale oil reservoirs; S1.

3. Use a cutting tool to cut the full-diameter flaky sample into shale samples of the required size in a direction perpendicular to the bedding and the bedding end surface.

4. The method for determining the porosity of shale oil samples in effective pore space according to claim 3, characterized in that: In the step S1, the cryo-prepared sample is frozen by liquid nitrogen.

5. The method for determining the porosity of shale oil samples in effective pore space according to claim 1 or 2, characterized in that: In step S2, the saturated liquid is anhydrous ethanol or kerosene.

6. The method for determining the porosity of shale oil samples in effective pore space according to claim 5, characterized in that: In the step S2, the saturated liquid of the shale sample without oil is anhydrous ethanol, and the saturated liquid of the shale sample containing oil is anhydrous ethanol or kerosene.

7. The method for determining the porosity of shale oil samples in effective pore space according to claim 6, characterized in that: In the step S2, t<T p (5) Where t is the longest time for sample self-absorption saturation; T p -The time it takes for the saturated liquid to penetrate into the clay adsorption layer or to produce cracks.

8. The method for determining the porosity of shale oil samples in effective pore space according to claim 7, characterized in that: In the step S2, Where: t is the maximum time of self-absorption saturation, t0 is the sample self-absorption saturation time corresponding to a certain stable time interval (Δt), is the average time used to test each sample, and n is the number of self-absorption saturated samples.

9. The method for determining the porosity of shale oil samples in effective pore space according to claim 1 or 2, characterized in that: In step S4, chloroform is used as a degreasing agent for degreasing the sample.

10. The method for determining the porosity of shale oil samples in effective pore space according to claim 9, characterized in that: In step S4, after the oil removal is completed, the sample and the sample bag are ventilated for 4 hours to 8 hours, and then the sample and the sample bag are placed in a vacuum drying oven, dried at 60° C. in vacuum for 8 hours, and then taken out.

Citation Information

Patent Citations

  • Method for measuring porosity of mud shale

    CN102252948A

  • Method for measuring total porosity of shale

    CN103344541A

  • Method for establishing complex pore shale rock physical model

    CN104007485A

  • Computing model of mud shale oil gas saturability

    CN104712329A

  • Evaluation method for hydrogen containing ingredient, porosity and aperture of shale rich in organic matters

    CN108458960A

Cited By

  • Method, device and equipment for measuring porosity of rock debris based on nuclear magnetic resonance

    CN121027197A